(untitled) (Research, Society and Development, 2021)
This article presents the scoping review protocol on allowing the sale of tobacco products only in tobacco stores in Brazil. It is based on the hypothesis that limiting the sale of tobacco products only in tobacco shops would significantly prevent initiation and encourage cessation, thus reducing smoking prevalence and passive smoking in Brazil. The protocol aims to document the processes involved in the planning and methodological approach of an extensive scoping review, guided by Joanna Briggs Institute’s manual. The review protocol was prepared following PRISMA Extension for Scoping Reviews (PRISMA-ScR): Checklist and Explanation. It was registered in the Open Science Framework.